Oncogenic Role of miR-483-3p at the IGF2/483 Locus - Veronese, Angelo (Cancer Res, 2010)
hsa-mir-483 is located within intron 2 of the IGF2 locus. We found that the mature microRNA (miRNA) miR-483-3p is overexpressed in 100% of Wilms’ tumors. In addition, colon, breast, and liver cancers exhibit high or even extremely high levels of miR-483-3p in ~30% of the cases. A coregulation with IGF2 mRNA was detected, although some tumors exhibited high expression of miR-483-3p without a concomitant increase of IGF2. These findings suggested that miR-483-3p could cooperate with IGF2 or act as an autonomous oncogene. Indeed, here we prove that an anti-miRNA oligonucleotide against miR-483-3p could inhibit the miRNAs without affecting IGF2 mRNA and it could suppress tumorigenicity of HepG2 cells, a cell line that overexpresses miR-483-3p and IGF2. Conversely, no antitumor effect was elicited by inhibition of IGF2. The oncogenic mechanism of miR-483-3p was at least partially clarified by the finding that it could modulate the proapoptotic protein BBC3/PUMA and miR-483-3p enforced expression could protect cells from apoptosis. Our results indicate that miR-483-3p could function as an antiapoptotic oncogene in various human cancers and reveal a new, potentially important target for anticancer therapy.